Exploring phenotypic variation of diverse bambara groundnut (Vigna subterranea L) origin and development of mini-core collection for future breeding - Uba, C.U.; Oselebe, H.O.; Tesfaye, A.; Mekonen, G.S.; Abtew, W.G. (Wiley, 2023)
Understanding the phenotypic variation and designing a mini-core collection is an efficient method to accelerate the genetic gain of bambara groundnut. A collection of 300 bambara groundnut landraces from 25 different countries of origin sourced from gene banks were used to analyze phenotypic variability among the landraces and develop a mini-core collection for future breeding. The landraces were evaluated in alpha lattice design with two replications for 2 years (2019 and 2020). The results showed highly significant differences (p < 0.001) among the bambara groundnut landraces for all the studied traits implying the selection of landraces with better agronomic traits could be achieved from the crop genetic pool. In addition, landrace x year interactions were significant for studied traits, except for shelling percentage and number of seeds per pod. The genotypic coefficient of variation values were high for most yield component traits, with the highest (65.39%) value obtained on seed dry weight. Furthermore, high heritability in conjunction with high genetic advance obtained in seed dry weight, pod dry weight, petiole length and plant height implies that these traits are majorly controlled by additive genetic action and could be improved through selection. Highly significant and positive correlations of yield were found with seed dry weight, pod dry weight, number of pod per plant, number of leaves, petiole length and plant height. A mini-core collection of 60 landraces (20%) was developed that represents the entire collection using Core Hunter algorithm. In general, the study provides insight into bambara groundnut germplasm that would enhance cultivar development and sustains the utilization of the crop. In addition, the mini-core collection established in the present study could be exploited for future bambara groundnut improvement efforts.